Nocturnal hypoglycaemia in ACTH and GH deficient children: role of continuous glucose monitoring. (6th May 2013) - Cambiaso, Paola; Schiaffini, Riccardo; Pontrelli, Giuseppe; Carducci, Chiara; Ubertini, Graziamaria; Crea, Francesca; Cappa, Marco
Summary Objectives To evaluate the usefulness of continuous glucose monitoring (CGM) to identify nocturnal hypoglycaemia in children affected by combined ACTH and GH deficiency and to optimize the hydrocortisone replacement therapy in these patients. Study design Eleven patients with ACTH and GH deficiency (five boys and six girls, age 1·6–16·8 years) underwent CGM for 36 h, including two nights. At least two consecutive glucose levels <2·78 mm were considered hypoglycaemic episodes. The differences in age and doses of hydrocortisone and recombinant human growth hormone (rhGH) between children with and without hypoglycaemia were analysed. The percentage of the glucose values <3·33 mm and the mean glucose levels were also evaluated. Results Continuous glucose monitoring demonstrated nocturnal hypoglycaemia lasting from 30 to 155 min (1·5% of the total monitoring time) in three cases (27%). No statistically significant differences in age and rhGH dose were observed between children with or without hypoglycaemia. Conversely, the difference in the hydrocortisone doses between the patients with and without hypoglycaemia resulted statistically significant (5·9 vs 8·5 mg/m²/day; P = 0·04). Eight patients presented glucose values less than 3·33 mm during 5% of the total monitoring time. Hydrocortisone dose showed significant positive linear relation with mean glucose level (r = 0·79, P = 0·0035) and inverse relation with time lags of glucose levels under 3·33 mm (r = −0·65, P = 0·03). Conclusions Our study shows that CGM may represent a valuable tool to detect nocturnal asymptomatic hypoglycaemic episodes and optimize the hydrocortisone therapeutic regimen in children with ACTH and GH deficiency.